PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN VARIABEL KEPUASAN KERJA SEBAGAI MEDIASI - Aswin, Angga Erly; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2017)
The purpose of this study was to determine the effect of perceived organizational support to organizational citizenship behavior with job satisfaction as a mediating variable in the Department of Industry and Trade of the Province of Bali. Samples taken as many as 63 respondents. The samples in this study using purposive sampling technique. The data collection is done by distributing questionnaires using 5-point Likert scale to measure 22 item statement. The analysis technique used is Path Analysis. The analysis showed that perceived organizational support positive and significant impact on organizational citizenship behavior, perceived organizational support positive and significant effect tehadap job satisfaction, job satisfaction positive and significant impact on organizational citizenship behavior, and this study also proved that the perceived organizational support affect the organizational citizenship behavior is mediated by job satisfaction in the Department of Industry and Trade of the Province of Bali.
Keywords: Perceived Organizational Support, Organizational Citizenship Behavior, Job Satisfaction